Interrelationships among predictors of lamb carcass composition - Cadavez, Vasco (2008)
The objective of th is study was to identify a reduced set of variables from an original data set of 18 carcass measurements in order to avoid redundancy, collinearity problems, and to simplify the development of models to predict lambs carcass composition. One hundred and twenty-six lambs, 86 mules and 40 females, of Churra Galega Bragançana Portuguese local breed were slaughtered, and carcasses were weighed (HCW) approximately 30 min after exsanguination. After cooling at 4°C tor 24 ha set of seventeen carcass measurements were recorded, and data interrelationships were analysed following the common factor analysis procedure. All variables were highly and positively correlated with HCW (r > 0.46), being especially high in the carcass dimensions measurements (r > 0.75). Subcutaneous fat thickness measurements were highly and positively correlated (r > 0.58) with breast bone tissues thickness measurements. Three common factors (factor I =carcass weight; factor 11 = subcutaneous fat thickness; factor Ill = breast bone tissues thickness) were retained, and accounted for 83.5% of the variation in the original variables. This study demonstrates that common factors analysis can be used to condense the information given by large sets of variables, allowing selecting a reduced number of variables, which contributes to reduce collinearity problems, and to simplify the development of models to predict lamb carcass composition